LANDSLIDE HAZARD MAPPING USING THE SCORE AND WEIGHT METHOD IN BANJARNEGARA - Muhammad Lulu Latif Usman; Bita Parga Zen; Zulfina Wiria Ananda; Siti Roqayah; Lintang Cahya Mulyadani; Bunga Laelatul Muna; Aprilia Intan Prasetya (Jurnal Teknik Informatika (Jutif), 2023)
Banjarnegara has a category of high or very vulnerable landslide susceptibility, according to data from the National Disaster Management Agency from 2006 to 2021, there has always been at least 1 landslide disaster in Banjarnegara. As a step in disaster reduction in Banjarnegara, a landslide hazard analysis was carried out. The methodology used is scoring and weighting using 4 indicators of rainfall, geology, land use, and slope. Landslide susceptibility is measured by calculating the total score which is then categorized based on the total score. The landslide susceptibility category is divided into 4 categories, namely Very Low, Low, Medium, and High. Areas with high vulnerability category have a proportion of 0.06% with an area of 682,073 m2, Medium has a proportion of 55.51% with an area of 625,539,155 m2, and Low has a proportion of 44.43% with an area of 500,730,369 m2. The results of the landslide hazard map can then be used as a reference for the Regional Disaster Management Agency to reduce the risk of landslide vulnerability.